2023
DOI: 10.1039/d2su00038e
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring lixiviant properties to optimise selectivity in E-waste recycling

Abstract: The presence of water in a DES imparts selectivity to metal etching via the formation of passivation layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…5–10 mPa s. Below this, etching rate decreases due to the high water (>30 mol water per kg of brine) and low chloride concentrations, resulting in poor solubility of the Ag + ions and the formation of AgCl precipitates. This effect of water content was also observed during the oxidation of silver in aqueous ChCl : 2EG using iodine [11] …”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…5–10 mPa s. Below this, etching rate decreases due to the high water (>30 mol water per kg of brine) and low chloride concentrations, resulting in poor solubility of the Ag + ions and the formation of AgCl precipitates. This effect of water content was also observed during the oxidation of silver in aqueous ChCl : 2EG using iodine [11] …”
Section: Resultssupporting
confidence: 55%
“…This switch between DES/IL with water dissolved in it and an aqueous solution of DES/IL components has also been observed for other types of DES and IL mixtures with water, via spectroscopic methods. The critical water content to cause changes in metal ion [3–4,6,13] or halide [11] speciation was 30–45 wt % in all cases described so far.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the case of iodine, it has been reported that both [I 2 Cl] − and [I 3 ] − are stable in ChCl: 2EG eutectic mixture (distribution between complexes tending to change as function of water addition) 72,73 , suggesting that both species should be able to oxidise iron according to equations 3 and 4. However, both the Fe III/II and iodine redox couples are at very similar potentials in ChCl: 2EG 52 , suggesting that Fe II can also be oxidised to Fe III by iodine.…”
Section: Chemical Etching Of "Campo Del Cielo" Meteoritementioning
confidence: 99%